Analisis Penetapan NJOP terhadap Harga Pasar dengan Metode Assessment Sales Ratio dalam Kaitannya dengan Potensi Pajak Bumi (Studi Kasus Tanah di Kecamatan Serpong Utara, Kota Tangerang Selatan) - Sally Nur Auliani; Kamio Kamio; Supadi Supadi (EKO-REGIONAL, 2012)
This research entitled “Analysis of Sales Worth for Taxable Properties Decision on Market Price with Assessment Sales Ratio Method in Accordance with Property Tax (Case Study in North Serpong Sub District South Tangerang City)”. The research aims to know whether assessment sales ratio has already appropriate with Property Tax Director decision, to know property tax potential that still can be collected by Regional Government, and to know whether Sales Worth for Taxable Properties has been equalize in all North Serpong Sub District area, in South Tangerang City. The research location was in North Serpong Sub District by using data of Sales Worth for Taxable Property and market price of land from 70 transactions in 2011. Descriptive was this research method by using simple random sampling as sampling method. By using assessment sales ratio analysis, central tendency, disperse coefficient measurement, and variation coefficientThe result shows that ASR value = 65.2%, which means ASR was not appropriate with standard from Property Tax Director and there was property tax potential for 14.8% up to 34.8% or for about Rp. 48,009,940.80 up to Rp. 113,099,860.80. COD variability measurement was 26.26% and COV was 34.51%, it means Sales Worth for Taxable Property of land in North Serpong Sub District was in unbalance standard.The implication was market price of land as the basic of Sales Worth for Taxable Property was dynamic and up-to-date, thus Serpong Tax Office Service (KPP) Pratama should making list of data, estimation, and reviewing individually. SO, the renewing and adjustment toward Sales Worth for Taxable Property decision based on market price should be observed to increase the property tax potential, and Serpong KPP Pratama should add estimating and data collecting officer in the field to balance the standard of decision on Sales Worth for Taxable Property. Keywords:Assessment Sales Ratio, COD, and COV